The witch in history : early modern and twentieth-century representations - Purkiss, Diane, 1961- (Routledge, 1996)
Looking at texts from colonial narratives to court masques, trial records to folktales, and Shakespeare to Sylvia Plath, this book shows how the witch acts as a carrier for fears, desires and fantasies both now and in the early modern period.